Time Calculation for Calcination of СаСОз Pieces - V. A. Sednin; A. G. Kogevnikov; I. V. Melnikov (Наука и техника)
The paper contains a model for calcination of calcite with varying thermal and physical parameters and internal source. The paper analyzes a model of thermal CaC03 dissociation.